2022
DOI: 10.3389/fimmu.2021.802795
|View full text |Cite
|
Sign up to set email alerts
|

PTRF/Cavin-1 as a Novel RNA-Binding Protein Expedites the NF-κB/PD-L1 Axis by Stabilizing lncRNA NEAT1, Contributing to Tumorigenesis and Immune Evasion in Glioblastoma

Abstract: BackgroundImmunotherapy, especially checkpoint inhibitors targeting PD-1 or PD-L1, has revolutionized cancer therapy. However, PD-1/PD-L1 inhibitors have not been investigated thoroughly in glioblastoma (GBM). Studies have shown that polymerase 1 and transcript release factor (PTRF/Cavin-1) has an immune-suppressive function in GBM. Thus, the relationship between PTRF and PD-L1 and their role in immune suppression requires further investigation in GBM.MethodsWe used public databases and bioinformatics analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Specific proteins are responsible for the stability of NEAT1, including HuR, LIN28B, ALKBH5, PTRF, ALYREF, and SRSF1 [ 158 , 161 , 162 , 163 , 164 , 165 ]. Specifically, HuR and LIN28B can promote ovarian cancer progression via stabilizing NEAT1 [ 161 , 164 ].…”
Section: Factors That Regulate Neat1 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific proteins are responsible for the stability of NEAT1, including HuR, LIN28B, ALKBH5, PTRF, ALYREF, and SRSF1 [ 158 , 161 , 162 , 163 , 164 , 165 ]. Specifically, HuR and LIN28B can promote ovarian cancer progression via stabilizing NEAT1 [ 161 , 164 ].…”
Section: Factors That Regulate Neat1 Expressionmentioning
confidence: 99%
“…Specifically, HuR and LIN28B can promote ovarian cancer progression via stabilizing NEAT1 [ 161 , 164 ]. In glioblastoma, PTRF can increase the stability of NEAT1 to promote cancer metastasis [ 165 ]. In addition, ALKBH5-stabilized NEAT1 can significantly suppress hypoxia-induced tumor-associated macrophage (TAM) recruitment and immunosuppression in glioblastoma [ 163 ].…”
Section: Factors That Regulate Neat1 Expressionmentioning
confidence: 99%
“…NEAT1 activates NF- κ B and PD-L1 to promote immune evasion by interacting with PTRF in glioblastoma [ 17 ] (p1) . On the other hand, numerous studies indicated that lncRNAs could also regulate necroptosis by acting as competitive endogenous RNA and influencing target gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting UBXN1 expression via NEAT1, PTRF enhanced PD-L1 transcription through promoting NF-κB activity. Finally, PTRF promoted immune escape of GBM cells though regulating PD-1 binding and PD-L1 mediated T cell toxicity [ 124 ].…”
Section: The Role Of Lncrnas In Immunotherapy In Different Tumorsmentioning
confidence: 99%